Social media stethoscope: unraveling how doctors’ social media behavior affects patient adherence and treatment outcome - Sun, Qian; Tang, Guiyao; Xu, Wenxiao; Zhang, Shaoli (Frontiers in Public Health, 2024)
Objective The exposure of the content posted by doctors on social media has the potential to influence how patients perceive and judge doctors. It is necessary to further investigate whether and how the content posted by doctors affects patients’ health behaviors and outcomes, as well as to identify the factors that may influence this mechanism. Methods Multi-respondent survey data was collected from 35 doctors and 322 patients in China, and structural equation modeling (SEM) was used to test the hypothesis model. Results The findings revealed that doctors posting professional knowledge content on social media positively impacted patient adherence and treatment effectiveness. Conversely, doctors sharing personal life-related content on social media were associated with lower patient adherence and poorer treatment outcome. Moreover, doctor gender and doctor humor moderate the relationship between social media behavior of doctors and patient adherence. Conclusion Doctors sharing professional knowledge on social media not only fosters trust in physicians but also closely correlates with patient adherence and treatment effectiveness.